Effects of hydrodynamic cavitation combined with snail enzyme treatment on the structure and functional properties of water-soluble dietary fiber in rice husks - Zhigang Quan; Mingming Chen; Dongjie Zhang (Ultrasonics Sonochemistry)
In this study, we adopted the synergistic modification technology of hydrodynamic cavitation and snail enzyme, to improve the yield and activity of soluble dietary fibers (SDFs) of rice husk. The physicochemical properties, structural changes, and inhibition of α-glucosidase and α-amylase of SDFs were examined in vitro. This synergistic treatment significantly increased the yield of SDFs to 18.64 % ± 0.16 %, significantly reduced the particle size to 122.33 ± 0.26 nm, and significantly increased the specific surface area to 1.718 ± 0.002 m2/g. The absolute value of the zeta potential significantly increased to −36.39 ± 0.12 mV, indicating an excellent solution stability and gel-forming ability. At the same time, the water-holding, oil-holding, and swelling capacities were significantly enhanced, reaching 8.52 ± 0.09 g/g, 4.85 ± 0.29 g/g, and 7.29 ± 0.25 mL/g, respectively. Structural analysis showed that the synergistic treatment destroyed the fiber structure, produced a large number of small molecule fragments, and significantly changed the monosaccharide components and functional group distribution. Functional evaluation showed that the inhibitory effect of CE-SDF on α-glucosidase and α-amylase was significantly enhanced, and enzymatic reaction kinetic analysis revealed that both enzymes were competitive inhibitors, with IC50 values of 2.893 and 1.727 mg/mL, respectively. In summary, the synergistic modification of hydrodynamic cavitation and snail enzyme greatly optimized the structural and functional properties of rice husk SDFs, providing a theoretical basis for its application in the field of hypoglycemic drugs and functional foods.